Molecular Identification of Trypanosma cruzi discrete Typing Units in end-Stage Chronic Chagas Heart Disease and Reactivation after Heart Transplantation - Burgos, Juan Miguel (2010)
One hundred years after the discovery of Chagas disease, it remains a major neglected tropical disease. Chronic Chagas heart disease is the most severe manifestation. Heart trasplantation is the proper treatment for end-stage heart failure. T. cruzi strains cluster into 6 discrete typing units assosiated with different geographical distribution, transmission cycles and varying disease symptoms.In the southern cone of South America, T. cruzi II, V and VI popuations appear to be assosiated with Chagas disease and T. cruzi I with sylvatic cycles.